MODERASI ISLAM: DARI KONSEP MENUJU IDENTITAS - Fadhliah Mubakkirah (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2018)
This paper seeks to present spirit as well as the concept of moderation in Islam to realize the identity and identity of Muslims in their daily lives. There are three styles of expressing Islam namely Left Extremist, Right Extremist and Wasathiyyah. Moderation is taken from this word, wasathiyyah. Moderation of Islam is a concept that teaches not to be extreme, radical, and excessive in religion. This is a characteristic of the Islamic religion. Islam always takes the "middle way" in its guidance. The face of Islam that is peaceful, moderate and tolerant will bring grace and peace to mankind.